Proceedings of the Fifth International Conference of Transportation Research Group of India 5th CTRG Volume 3 - Parida, Manoranjan; Maji, Avijit; Velmurugan, S.; Das, Animesh; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book (in three volumes) comprises the proceedings of the Fifth Conference of Transportation Research Group of India (CTRG2019) focusing on emerging opportunities and challenges in the field of transportation of people and freight. The contents of the volume include characterization of conventional and innovative pavement materials, operational effects of road geometry, user impact of multimodal transport projects, spatial analysis of travel patterns, socio-economic impacts of transport projects, analysis of transportation policy and planning for safety and security, technology enabled models of mobility services, etc. This book will be beneficial to researchers, educators, practitioners and policy makers alike.
Keywords: Transportation engineering; Traffic engineering; Engineering -- Data processing; Buildings -- Design and construction; Quantitative research; Transportation Technology and Traffic Engineering; Data Engineering; Building Construction and Design; Data Analysis and Big Data; Transportation -- Congresses